A Novel Mechanism Underlying Inflammatory Smooth Muscle Phenotype in Abdominal Aortic Aneurysm. Issue 10 (23rd September 2021) - Cai, Dunpeng; Sun, Chenming; Zhang, Gui; Que, Xingyi; Fujise, Ken; Weintraub, Neal L; Chen, Shi-You
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Abdominal aortic aneurysm (AAA) is a permanent and localized dilatation of abdominal aorta with potentially fatal consequence of aortic rupture. No effective pharmacological approach has been identified to limit AAA progression and rupture. AAA is characterized by extensive aortic wall matrix degradation that contributes to arterial wall remodeling and eventual rupture, in which smooth muscle cell (SMC) phenotypic transition and MMPs (matrix metalloproteinases), especially MMP2 (matrix metalloproteinase-2) and MMP9, play critical roles. Objective: Our previous study showed that ADAR1 (adenosine deaminases acting on RNA 1) regulates SMC phenotype, which prompted us to study if ADAR1 is involved in AAA development. Methods and Results: We used Ang II (angiotensin II) infusion ApoE −/− mouse model combined with ADAR1 global and SMC-specific knockout to study the role of ADAR1 in AAA formation/dissection. Aortic transplantation was conducted to determine the importance of vascular cell ADAR1 in AAA development/dissection. Primary cultured SMC were used to study how ADAR1 regulates the inflammatory SMC phenotype and MMP production/activity. Patient specimens were obtained to investigate the relevance of ADAR1 expression to human AAA disease. ADAR1 was induced in abdominal aortic SMC in both mouse and human AAA tissues. Heterozygous knockout of ADAR1 diminished the Ang II–induced AAA/dissection in ApoE −/− mice. Mouse aortic transplantation showed that ADAR1 in vascular cells was essential for AAA formation. SMC-specific ADAR1 knockout reduced experimental AAA formation/dissection. Mechanistically, ADAR1 interacted with HuR (human antigen R) to increase the stability of MMP2 and MMP9 mRNA, leading to increased MMP levels and activities. Conclusions: ADAR1 is novel regulator of AAA development/dissection, and thus may represent a potential new therapeutic target to hinder AAA growth and rupture.